2020
DOI: 10.3389/fgene.2020.543890
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Genetic and Genomic Analyses of Combined Health Data Across Ecotypes to Improve Disease Resistance in Indigenous African Chickens

Abstract: Poultry play an important role in the agriculture of many African countries. The majority of chickens in sub-Saharan Africa are indigenous, raised in villages under semi-scavenging conditions. Vaccinations and biosecurity measures rarely apply, and infectious diseases remain a major cause of mortality and reduced productivity. Genomic selection for disease resistance offers a potentially sustainable solution but this requires sufficient numbers of individual birds with genomic and phenotypic data, which is oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
(70 reference statements)
1
9
1
Order By: Relevance
“…For instance, according to Liu et al (2014), many significant markers were found to influence innate and adaptive immune traits in chicken but none of them could explain more than 5% of the observed phenotypic variances. In view of these observations, Banos et al (2020) suggest that genome-wide association studies in tropically adapted chicken would also be necessary in order to identify more genes involved in immune-related traits and possibly aid in proposing efficient selection strategies for such populations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to Liu et al (2014), many significant markers were found to influence innate and adaptive immune traits in chicken but none of them could explain more than 5% of the observed phenotypic variances. In view of these observations, Banos et al (2020) suggest that genome-wide association studies in tropically adapted chicken would also be necessary in order to identify more genes involved in immune-related traits and possibly aid in proposing efficient selection strategies for such populations.…”
Section: Discussionmentioning
confidence: 99%
“…The natural relative resistance of these breeds could be attributed to hygiene practices. Therefore, these birds might have undergone long-term natural selection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MAP3K21 is an NIH designated IDG-eligible kinase. Existing reports identify a correlation between MAP3K21 and pediatric obesity, E. coli induced diarrhea, and disease resistance in African chickens [150][151][152].…”
Section: Map3k21mentioning
confidence: 99%